PENGARUH KEPEMIMPINAN, MOTIVASI, KEADILAN ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLA KEUANGAN ASET DAN PENDAPATAN DAERAH KABUPATEN MUNA BARAT - La Ida; Dedy Takdir Syaifuddin; Murdjani Kamaluddin; Sudirman Zaid (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to explain and examine the influence of leadership on employee performance, motivation on employee performance, organizational justice on employee performance, and job satisfaction on employee performance. This research approach is a survey. The data was collected in a cross-sectional manner using an instrument in the form of a questionnaire. The population in this study were all Civil Servants (PNS) and Non-PNS as many as 98 people. The sampling technique is a saturated sample (census) where the entire population is used as the research sample. The data analysis technique to answer the research hypothesis is Partial Least Square (PLS).The results showed that leadership had a significant effect on employee performance, motivation had a significant effect on employee performance, organizational justice had a significant effect on employee performance, and job satisfaction had a significant effect on employee performance.